Development and Psychometric Evaluation of a Spiritual Self-care Scale for Iranian Adolescents - Hekmati-pour, Nafiseh (Journal of religion and health, 2025)
This study aimed to develop and psychometrically validate a spiritual self-care tool for Iranian adolescents in 2019. The study utilized an exploratory mixed method approach, which included directed content analysis, item development, scale development, scale evaluation and examination of scale stability. During the qualitative phase, 170 items were initially extracted; these items were then reduced and refined to 59 items through scale development, content validity ratio and content validity index assessments. In terms of construct validity, the Kaiser-Meyer-Olkin test yielded a value of 0.813 and Bartlett’s test of sphericity was found to be significant (p < 0.001). Subsequently, the confirmatory factor analysis was conducted in a separate sample, resulting in a final model with 34 items and eight factors. The model demonstrated a moderate fit, with a Cronbach’s alpha value of 0.76 for the final version of the scale. As a result, the adolescents’ spiritual self-care scale is considered a valid and reliable tool for measuring spiritual self-care.